Legacy in Collaborative Research: Reflections on a Community Research Project - Jenny Barke; Simon Hankins (Journal of Community Engagement and Scholarship, 2022)
This article reflects on the legacy of a collaborative community research project which explored loneliness amongst older people. Six years after completing the original research, the authors reviewed their learning from the project to consider how impactful legacy can be developed and supported in community/university research partnerships. Three key features are identified within the article. First the importance of talking about legacy from the start of a project. Second, genuine ownership of a project is a gradual and deliberate process, and third, time continuity and funding are needed to support legacy. The authors suggest that a deliberately planned process empowered collaborators to actively engage with and use the research findings to develop interventions and support change in the community.